Fidelity of Implementation in the Field of Learning Disabilities. (November 2019) - Sanetti, Lisa M. Hagermoser; Luh, Hao-Jan
Decades of research and billions of dollars have been spent to develop and evaluate evidence-based interventions and develop multitiered systems of support (MTSS) toward the goal of more effectively delivering interventions and improving student outcomes. Available evidence, however, suggests interventions are often adopted slowly and delivered with poor fidelity, resulting in uninspiring outcomes for students. The field of implementation science has emerged to address the science-to-practice gap in human service sectors (e.g., education) as a way of improving service recipient (e.g., student) outcomes. For the considerable investment in school-based intervention development and evaluation to have a significant public health impact for students, educators must integrate key findings from implementation science into their practice and research. Toward this end, the purpose of this article is four-fold. First, it overviews implementation science and implementation theories, models, and frameworks. Second, it discusses the relevance of implementation science and fidelity to both the systems-level implementation of MTSS and individual-level implementation of interventions to students with learning disability (LD). Third, it reviews the unique legal aspects related to service implementation for students with LD and the gap between state-level mandates and available science. Finally, it provides additional resources and recommendations for readers.